Pengembangan Tepung Sukun dan Tepung Kacang Tunggak dalam Pembuatan Kue Mangkok - Inggita Erlita Yusuf (Universitas Muhammadiyah Semarang, 2022)
Nutrient intake has an important role in human growth and development. Therefore it is necessary to make an alternative effort f of snacks that can contribute to protein, carbohydrate and fat intake. In fulfilling nutritional intake, it is necessary to regulate a food menu by selecting types of food items with high nutritional value and good for body health. Purpose of this study is to analyze of acceptability, proximate with an addition of breadfruit flour and cowpea flour. This study is experimental study comparing all of formulation of breadfruit flour and cowpea flour added to kue mangkok is F0 (TS= 0 g ; TKT= 0 g), F1 (TS= 32 g ; TKT= 48 g), F2 (TS= 40 g ; TKT= 40 g) dan F3 (TS= 48 g ; TKT= 32 g). This data were processed using One Way Anova with Duncan's continued test. Results of the nutritional content of kue mangkok is Moisture content 51.02 g, ash content 0.67 g, protein 4.41 g, total fat 16.85 g, carbohydrate 27.03 g. The formula’s chosen by the best formula. The conclusion of this study, there are significant differences in proximate of kue mangkok with the addition of breadfruit flour and cowpea flour.